Seeds We Sow - Lai, Gerald Sze Hang (Nanyang Technological University, 2023)
Local produce of a country can be means of nation-branding as locally-grown food are cultural products that reflect the taste and preference of natives. They cultivate a sense of belonging and emotionally connect consumers with the origins of their food. Seeds We Sow examines Singapore’s agri-food industry to uncover how fresh food is produced and visually represented, to explore new ways of representing local produce that will emotionally appeal to consumers and generate a sense of pride. As part of the project, Farm Folio is an archive of farms in Singapore, documenting existing visual representations of local produce, such as fresh products, packaging designs, point-of-sales displays and behind-the-scenes processes that are hidden from consumers. The archive aims to shine a light on the hard work that goes into producing Singapore’s fresh produce and generate greater appreciation for the industry.